The The impact of vitamin D on muscle function and bone health in postmenopausal women - Katarzyna Agopsowicz; Katarzyna Blicharz; Anna Bieniasz; Michalina Piwowar; Anna Zdziebło; Martyna Biernacka; Dominika Stolarczyk; Katarzyna Zdziebło; Piotr Mojżesz; Igor Biernacki (Quality in Sport)
The role of vitamin D in preserving muscle function and bone health in postmenopausal women has gained significant scientific interest. Menopause, characterized by a decline in estrogen levels, heightens the risk of osteoporosis and sarcopenia, significantly affecting mobility and quality of life. It is also associated with various physiological changes, such as hot flashes, mood disturbances, sleep irregularities, and an increased likelihood of musculoskeletal decline. (Sharma M et al. 2024; Santoro N et al. 2021; Santoro N et al. 2015). Vitamin D plays a pivotal role in calcium homeostasis, bone remodeling, and muscle function. However, its deficiency is widespread among postmenopausal women and has been linked to decreased bone mineral density, heightened fracture susceptibility, and diminished muscle performance. Although vitamin D supplementation is frequently recommended to mitigate these effects, its efficacy in enhancing musculoskeletal health remains a subject of debate. Recent studies have identified vitamin D receptors (VDR) in human muscle tissue, supporting the hypothesis that vitamin D contributes to muscle cell proliferation, differentiation, and function (Iolascon G et al. 2018). Despite these findings, inconsistencies in research outcomes and gaps in understanding the physiological mechanisms of vitamin D’s action highlight the need for further investigation into how different levels of vitamin D influence musculoskeletal health and overall well-being in menopausal women. This review evaluates evidence on vitamin D’s impact on muscle strength, bone density, and fracture risk in postmenopausal women, focusing on its therapeutic potential.